Design and development of a virtual reality anatomy medical classroom by utilizing cognitive load theory and the virtual medical technology acceptance model (VMEDTAAM) - Muhammad Aminuddin Akmal Mohd Hamizi; Nur Azlina Mohamed Mokmin; Ummie Haniffah Ariffin (Pejabat Karang Mengarang UPSI, 2023)
Without a doubt, medical sciences have a significant effect on our lives. The medical sciences aid in the diagnosis and treatment of diseases and ailments. According to studies, the majority of students utilized conventional instructional methods in their practical classroom. Virtual reality is one of the immersive technologies that aid the learning process by reducing cognitive load. According to Mayer's 12 Multimedia Principles, the learning process is enhanced when multimedia elements such as visuals audio are combined. This study presented the design and development of a VR anatomy medical classroom by employing cognitive load theory and determining the acceptability of virtual reality technology for the medical sciences. The combination of the ADDIE model and 12 Mayer's Principle of Multimedia improved the learning method and research framework for the use of VR-based technologies in medical sciences education. Utilizing a modified version of the Technology Acceptance Model (TAM), the VMedTAAM is used to determine the acceptance of technology in medical education. The result will serve as a guide for future VR developers to improve the design of immersive technology in this area.